Gradual Implementation of Smart Management Principles in The Higher Education System of Uzbekistan - Dilshodbek Toshpulatov; Bahodirjon Nosirov; Turgunboy Khalmatov (Research Parks Publishers, 2021)
This article discusses the reasons for the implementation of smart management methods in the higher education today and their gradual implementation in practice. A systematic approach is predominant in education management at all levels. Other criteria for evaluation of higher education (efficiency, acceptability, etc.) are considered in close connection with the overall success of the strategy of the higher education institution in the market of educational services in Uzbekistan and the world. The end result of evaluating the effectiveness and acceptability of a higher education institution is the management of the university, which is ultimately determined by the high quality of education.